Pengaruh Penggunaan Media Boneka Tangan Terhadap Kemampuan Bercerita Siswa Kelas V Sd Negeri Silih Asuh III Kota Cirebon - Roheni; Yuda Nuryenda, Endang; Syahbani, Aisyah (Jurnal Ilmu Pendidikan Dasar (JIPDA), 2024)
This study aims to investigate the use of puppet media and to determine the extent of its impact on the storytelling skills of fifth-grade students at SD Negeri Silih Asuh III in Cirebon City. Using a quantitative approach, the research employs a one group pretest-posttest design. The sample consists of one class with 20 students who were tested before and after the implementation of puppet media. Data were collected through a storytelling test administered in three stages: pretest, treatment, and posttest. Data analysis indicates an improvement in students’ storytelling abilities after the treatment using puppet media, with an average pretest score of 58.5 and a posttest score of 91. The t-test results showed a significance value of 0.000. Since the significance value is less than 0.05, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. These findings suggest that puppet media can enhance students’ storytelling skills and provide a more engaging learning experience. The study recommends that teachers consider using puppet media in Indonesian language lessons to improve students’ storytelling abilities and encourages further research on innovative teaching media